A cryptic variation in a member of the Ovate Family Proteins is underlying the melon fruit shape QTL fsqs8.1 - Cecilia Martínez-Martínez; Maria José Gonzalo; Pablo Sipowicz; Manuel Campos; Irene Martínez-Fernández; Carmen Leida; Mohammed Zouine; Konstantinos G. Alexiou; Jordi Garcia-Mas; María Dolores Gómez; Pablo Tornero; Miguel Ángel Pérez-Amador; et al. (Theoretical and Applied Genetics, 2022)
Key message The gene underlying the melon fruit shape QTL fsqs8.1 is a member of the Ovate Family Proteins. Variation in fruit morphology is caused by changes in gene expression likely due to a cryptic structural variation in this locus. Abstract Melon cultivars have a wide range of fruit morphologies. Quantitative trait loci (QTL) have been identified underlying such diversity. This research focuses on the fruit shape QTL fsqs8.1 , previously detected in a cross between the accession PI 124112 (CALC, producing elongated fruit) and the cultivar ‘Piel de Sapo’ (PS, producing oval fruit). The CALC fsqs8.1 allele induced round fruit shape, being responsible for the transgressive segregation for this trait observed in that population. In fact, the introgression line CALC8-1, carrying the fsqs8.1 locus from CALC into the PS genetic background, produced perfect round fruit. Following a map-based cloning approach, we found that the gene underlying fsqs8.1 is a member of the Ovate Family Proteins (OFP), CmOFP13, likely a homologue of AtOFP1 and SlOFP20 from Arabidopsis thaliana and tomato, respectively. The induction of the round shape was due to the higher expression of the CALC allele at the early ovary development stage. The fsqs8.1 locus showed an important structural variation, being CmOFP13 surrounded by two deletions in the CALC genome. The deletions are present at very low frequency in melon germplasm. Deletions and single nucleotide polymorphisms in the fsqs8.1 locus could not be not associated with variation in fruit shape among different melon accessions, what indicates that other genetic factors should be involved to induce the CALC fsqs8.1 allele effects. Therefore, fsqs8.1 is an example of a cryptic variation that alters gene expression, likely due to structural variation, resulting in phenotypic changes in melon fruit morphology.